DIFFERENCE OF POWER TEST AND TYPE II ERROR (β) ON MARDIA MVN TEST, HENZE ZIKLER'S MVN TEST, AND ROYSTON'S MVN TEST USING MULTIVARIATE DATA ANALYSIS - Wahyul Anis; Kuntoro Kuntoro; Soenarnatalina Melaniani (Universitas Airlangga, 2021)
The Mardia MVN test, Henze Zikler's MVN test, and Royston's MVN test are the most widely used tests to analyze multivariate normal (MVN) data, but there have not been many studies explaining the advantages and disadvantages of these tests. The research objective was to analyze the difference in test strength and type II (β) error in the Mardia MVN test, Henze Zikler's MVN test, and Royston's MVN test. The research data were analyzed using three MVN tests, namely the Mardia MVN test, Henze Zikler's MVN test, and Royston's MVN test. The results of the analysis in the form of test strength and type II error (β) would be compared at alpha (α) 1%, 5%, 10%, 15%, 20%, and 25%. The comparison results explained that the Mardia test had the greatest test strength and the smallest type II (β) error. The study concluded that the Mardia MVN test was a multivariate normal test better than Henze Zikler's MVN test and Royston's MVN test.